A Guide and Advice for Economists on the U.S. Junior Academic Job Market: 2014-2015 Edition - John H. Cawley (Institute for the Study of Labor (IZA), 2014)
This guide, updated for the 2014-15 job market season, describes the U.S. academic market for new Ph.D. economists and offers advice on conducting an academic job search. It reports findings from published papers, describes practical details, and provides links to internet resources. Topics addressed include: preparing to go on the market, applying for academic jobs, the AEA's new electronic clearinghouse for the job market, signaling, interviewing at the ASSA meetings, campus visits, the secondary market scramble, offers and negotiating, diversity, and dual job searches.
Keywords: A11; A23; J0; J44; 330; benefits; academic labor market; market for economists; salaries